Learning And Teaching In Digital Age - zulhendri; Jamaris; Solfema (CV. AFDIFAL MAJU BERKAH, 2021)
The purpose of this study is to find out the use of technology for teaching and learning in digital area. The research method is literature review or literature study, which contains theories relevant to research problems. The result of the use of technology for teaching and learning in digital area are Computer-Based Learning, computer networking, Online learning environment, Social Media and a paradigm shift. Learning in the digital era is complex and dynamic since it involves mix of work, social life and education system that we need to understand alongside the different theories of education and learning.